2009
DOI: 10.1243/09576509jpe757
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a centrifugal pump running in reverse mode

Abstract: This article reports a work on the three-dimensional flow simulation in a centrifugal pump operating in reverse mode. The simulations were carried out with the commercial code Fluent using unsteady flow calculations together with a sliding mesh technique. Hence, it was possible to account for the effect of blade—tongue interactions on the local flow. The numerical predictions were compared with the experimentally determined performance characteristics and also with the static pressure distribution obtained aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Most of the researchers have studied the performance in pump and turbine modes, either experimentally [15,32] or numerically [18,44], at same rotational speed. Usually, best efficiency point (BEP) of pump running in turbine mode is obtained at higher head and discharge compared to that in pump mode [4,14,18,45,46].…”
Section: Effects Of Rotational Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the researchers have studied the performance in pump and turbine modes, either experimentally [15,32] or numerically [18,44], at same rotational speed. Usually, best efficiency point (BEP) of pump running in turbine mode is obtained at higher head and discharge compared to that in pump mode [4,14,18,45,46].…”
Section: Effects Of Rotational Speedmentioning
confidence: 99%
“…Nourbakhsh [32], Yang et al [43], Fernandez et al [44], Morros et al [47], Sheng et al [53], Sedlar et al [54], Yang et al [58] as shown in Fig. 21(b), which was found to vary in the range of ±13%.…”
Section: Development Of Correlationmentioning
confidence: 99%
“…On the other hand, one of the main limitations in the use of PATs arises from the little knowledge about their performance and their internal behavior in both steady and transient conditions, because the characteristic curves are rarely provided by manufactures. Several literature studies proposed various methods to overcome such limitation, relying on either experimental testing [8][9][10] or numerical simulations [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several models were developed based on the Computational Fluid Dynamics (CFD) technique, which couples the Reynolds Averaged-Navier Stokes (RANS) equations with turbulence models. Avoiding the significant time-demand and the expensive costs related to the experimental researches, CFD models allow both the performance prediction [11][12][13] and the flow field calculation, allowing the investigation of secondary flows, internal head losses, generated force and torque and cavitation [14]. Furthermore, the optimization of the performance of the machine is also possible by simulating different geometrical configurations [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…They represent an alternative to micro-turbines, providing interesting efficiencies and significant working conditions, at the expense of lower investment and maintenance costs. In the literature, due to the limited information about the PAT performances provided by manufactures, several theoretical [1], experimental [2][3][4] and numerical [5,6] models were proposed to assess the PAT characteristic curves at different operations.…”
Section: Introductionmentioning
confidence: 99%